Tinjauan Fikih Muamalah Terhadap Sistem Bagi Hasil Usaha Keramba Jaring Apung Desa Merangin Kecamatan Kuok Kabupaten Kampar - Budiman Budiman; Daharmi Astuti (SERAMBI: Jurnal Ekonomi Manajemen dan Bisnis Islam, 2020)
Purpose: This study aims to determine the contract system used and the profit-sharing system of floating net cages in Merangin Village, Kuok District, Kampar Regency. Method: field research using a descriptive qualitative analysis approach. Data collected through interviews and direct observation. Finding: the results of the study revealed that in the practice of floating net cage fish cages between cage owners and employees namely Syirkah Mudharabah, in terms of the legal aspects of the Mudharabah Syirkah, the Rukun Syirkah Mudharabah, Terms, Principles, Contracts and Profit Sharing (profits and losses) that contained in the study of Muamalah Jurisprudence. Implication: socialization about business cooperation needs to be carried out in the perspective of the Shari'ah by relevant parties, to increase the understanding of the local community about the concept of business cooperation following Islamic Shari'ah